Android-Based Dental and Oral Health Diagnostic Expert System - Kamila, Marcia; Tanamal, Rinabi (Teknik Informatika Universitas Pamulang, 2018)
Dental and oral health is one of the most crucial thing for human health. If it is taken cared properly then all foods will be absorbed optimaly and human body will have all the nutritions needed. Otherwise, if it is not taken cared properly then it will affects health condition of a human body. Lack of awareness of Indonesians about their dental and oral health had caused many of infection cases which leads to teeth structural damage. In 2013, Health Research and Development Agency had done a survey based on interview’s result. They found that 25,9 percent of people in Indonesia were having issues with their dental and oral health in the last 12 months. Among them, there was 68,8 percent people who had not taken an treatments. To resolve this problem, expert system with android platform is made to diagnose dental and oral diseases. The research methodology used is forward chaining method. Expert System Shell used is CLIPS which then adopted into Android application.